Disinflation and the Recession-Now-Versus-Recession-Later Hypothesis : Evidence From Uruguay - Vegh Gramont, Carlos (IMF Working Papers; Working Paper ;, 1995)
Both analytical models and casual empiricism suggest that the timing of the recessionary costs associated with inflation stabilization in chronic inflation countries may depend on the nominal anchor which is used. Under money-based stabilization, the recession occurs at the beginning of the program, while under exchange rate-based stabilization the recession occurs later in the program. This paper provides a first attempt to formally test this hypothesis using a vector-autoregression model for Uruguay. The impulse response of output to different stabilization policies is broadly consistent with the 'recession-now-versus-recession-later' hypothesis. The evidence also suggests, however, that the effectiveness of a monetary anchor in reducing inflation is hindered by the high degree of dollarization of the Uruguayan economy.